(untitled) (Proceedings of International Conference on Special Education, 2017)
LINUS was a new extension of the KIA2M for continuing their objectives and purposes. Factors such as socioeconomic, classroom management style and teaching style are often overlooked. Thus, students’ LINUS achievement has become an important issue to be studied. The purpose of this study was to investigate the relationship among LINUS students’ socioeconomic, teachers’ classroom management style and teachers’ teaching style in teaching LINUS subjects, Bahasa Melayu and Mathematics. The research site was elementary schools in the eastern zone of Kluang, Johor. This study used the quantitative method which using questionnaire as the tool for the data collection. Cluster random sampling method was applied in the selection of 102 as research respondents. All the statistical analysis performed by using Statistical Package for Social Sciences version 20 (SPSS 20.0). The quantitative data was analyzed through descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistic involving parametric test (Rank Biserial Correlation). A pilot test was carried out for Behavior and Instructional Management Scale (BIMS) and Teaching Style (TSI) with the Cronbach’s Alpha coefficient values of 0.815 and 0.837 respectively. In descriptive analysis, the study found that the highest proportion in education, occupation and income were middle school, labor business and salary between RM 2001 to RM 3001. Majority of parents’ background had lowered socioeconomic. In addition, the dominant levels of classroom management style and teaching style obtained high mean scores according to interpretive scale. The inferential analysis results found little significant relationship between LINUS students’ socioeconomic status and measures of LINUS achievement and non-significant relationships were found between elementary school teachers’ classroom management and teachers’ teaching style and student LINUS achievement.